Sexual Selection of Scorpions: -An example of patterns and mechanisms in a Neotropical species- - Peretti, A. V. (2017)
Fil: Peretti, A. V. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.